Generations X and Y Attitude towards Controversial Advertising - Ting, Hiram; Ernest Cyril , de Run (Asian Journal of Business Research, 2012)
Segmentation has been useful in advertising decisions and subsequently the generation approach has emerged as a superior segmentation approach. The purpose of this article is to examine the attitudes of generation X and generation Y towards controversial advertising. Structured questionnaires were distributed throughout Malaysia, and a total of 768 usable questionnaires were obtained. Findings show that the two generational cohorts are significantly different in attitude towards controversial advertising. Generation X found the advertising of female contraceptives, feminine hygiene products, and funeral services to be more controversial, whereas generation Y found the advertising of alcoholic products, condoms, and gambling to be more of a controversy. In terms of the reasons of controversy, generation X found only health and safety issues to be more controversial whereas generation Y, hard sell, nudity, racist images, sexist images, and subject too personal. Future studies are therefore needed to validate the segregation of generations in Malaysia to secure effective marketing strategy.